2012
DOI: 10.1016/s0019-4832(12)60096-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Bangladesh: a review

Abstract: A B S T R A C THypertension (HTN) is an increasingly important medical and public health problem. In Bangladesh, approximately 20% of adult and 40-65% of elderly people suffer from HTN. High incidence of metabolic syndrome, and lifestyle-related factors like obesity, high salt intake, and less physical activity may play important role in the pathophysiology of HTN. The association of angiotensin-converting enzyme (ACE) gene polymorphism and low birth weight with blood pressure has been studied inadequately. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 26 publications
7
68
1
Order By: Relevance
“…The reported prevalence varies widely from 1.21% to 32%. 11,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 2). According to the Bangladesh NCD Risk Factor Survey 2010 27 , the prevalence of hypertension is 17.9% in general, 18.5% in men and 17.3% in women.…”
Section: Methodsmentioning
confidence: 99%
“…The reported prevalence varies widely from 1.21% to 32%. 11,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 2). According to the Bangladesh NCD Risk Factor Survey 2010 27 , the prevalence of hypertension is 17.9% in general, 18.5% in men and 17.3% in women.…”
Section: Methodsmentioning
confidence: 99%
“…A Bangladeshi study reported the prevalence of hypertension 65% in general, 75% in urban and 53% in rural areas. 7 A recent study among senior citizens showed that 44.8% were hypertensive. 8 Another study reported that hypertension is equally prevalent in rural population 9 among the diabetics, the prevalence of systolic hypertension was 23.2% and diastolic hypertension 13.6%.A recent study by Shariful Islam and colleagues showed that systolic hypertension was significantly associated with diabetes complications [OR 0.809, 95% CI 0.666-0.981 (p-value 0.031) after controlling for all other effect.…”
Section: Introductionmentioning
confidence: 99%
“…10 Overweight, sedentary lifestyle, unhealthy diet, salt intake, diabetes and smoking are among the common risk factors for hypertension in Bangladesh. 6,7 Hypertension and its complications, which are mostly preventable though simple health promotion and preventive measures, pose a serious threat to the health systems and socio-economic condition of a country. Hypertension prevention therefore is of great public health importance in Bangladesh and other developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…So, it can be said that people who took extra salt in their food may be prone to develop hypertension which is similar to other studies in Bangladesh and India. 11,12 A study showed that participants who took extra salt had almost 1.5 times higher risk of hypertension. 5 Another recent study showed that in 2010, globally 1.7 million deaths occurred from cardiovascular causes that were attributed to excess sodium consumption above a reference level of 2.0 gm per day.…”
Section: Table 3 the Respondents By The Time Of Being Identified As mentioning
confidence: 99%
“…11,12 Furthermore, it was shown that the risk of developing hypertension was significantly higher among smokers and smokeless tobacco users. 5 Another study in Bangladesh found a higher prevalence of smoking and showed an increased risk of coronary heart diseases was approximately four folds than ever smokers.…”
Section: Table 3 the Respondents By The Time Of Being Identified As mentioning
confidence: 99%